PENGARUH PERSEPSI ETIKA, PENGALAMAN KERJA, DAN TIPE KEPRIBADIAN TERHADAP KEMAMPUAN AUDITOR MENDETEKSI KECURANGAN - Tandijono, Vania; Rahayu, Mudjilah; Febrina, S, Patricia (Jurnal Akuntansi Kontemporer, 2018)
Cases of fraud that have occurred in Indonesia have occurred a lot which resulted in considerable losses to the community. This study aims to obtain empirical evidence and analyze the influence of ethical perceptions, work experience, and personality type on the auditor's ability to detect fraud through professional skepticism. This type of research includes testing hypotheses by using primary data through questionnaires. Population and sample are chosen for this study were independent auditors, namely the Public Accounting Office (KAP) in Surabaya. Based on the directory of the Indonesian Institute of Certified Public Accountants (IAPI) in 2017, there are around 44 KAPs in Surabaya that are the object of research. Data collection techniques in this study used purposive sampling and convenience sampling. The data analysis technique used in this study is SEM (Structural Equation Model) with SmartPLS 3.0 (Partial Lease Square) program. The results showed that ethical perceptions, work experience, and personality types did not influence the auditor's ability to detect fraud through professional skepticism.